Polyurethane foam and vehicle soundproofing material

A polyurethane foam with a dense skin and internal foam layer addresses the low frequency sound absorption issue, achieving high sound absorption coefficients in thin applications like vehicle fender liners and undercovers, reducing manufacturing costs and mass.

JP7601009B2Active Publication Date: 2024-12-17AGC INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021567572
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-26
Filing Date
2020-12-23
Publication Date
2024-12-17
Estimated Expiration
2040-12-23

AI Technical Summary

Technical Problem

Existing polyurethane foams lack sufficient sound absorption performance in the low frequency range (500Hz or lower) when used alone, and composite materials with other substances increase manufacturing costs and mass, making them unsuitable for thin applications like vehicle fender liners and undercovers.

Method used

A polyurethane foam with a dense skin layer and internal foam layer, having specific skeletal ratios and densities, achieving sound absorption coefficients of 0.40 or more at 1000Hz thickness of 10mm, suitable for thin applications.

Benefits of technology

The polyurethane foam provides excellent sound absorption in the low frequency range of 500 to 2000Hz, even when thin, making it suitable for vehicle soundproofing materials, particularly in fender liners and undercovers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601009000001
    Figure 0007601009000001
  • Figure 0007601009000002
    Figure 0007601009000002
  • Figure 0007601009000003
    Figure 0007601009000003
Patent Text Reader

Abstract

Provided are: a polyurethane foam having a good sound absorption coefficient in a low-frequency band of 500-2000 Hz, enabling weight reduction while maintaining sound absorption performance equivalent to or higher than that of conventional products, and having a skin layer that can be used as a soundproofing material for a vehicle; and a soundproofing material for a vehicle. This polyurethane foam and this soundproofing material for a vehicle each have a skin layer and an internal foam layer formed inside the skin layer, a thickness of 3-25 mm, a normal incidence sound absorption coefficient at a frequency of 1000 Hz of not less than 0.40 at a thickness of 10 mm, and a skeleton coefficient ratio SS / SI of 2.8-5.0 where the skeleton coefficient of the skin layer is defined as SS and the skeleton coefficient of the internal foam layer is defined as SI.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyurethane foam and a soundproofing material for vehicles. [Background technology]

[0002] Vehicles such as automobiles are fitted with soundproofing materials as undercovers or fender liner covers in order to suppress noise from motors, engines, tires, etc. to the outside of the vehicle. Polyester fiber or polyolefin fiber nonwoven fabric or polyurethane foam is used as the soundproofing material. Polyurethane foam is less expensive than polyester fiber and polyolefin fiber, but since it lacks sound absorbing performance in the low frequency range when used alone, it has been used as a composite with a sheet of rubber, thermoplastic elastomer, or thermoplastic resin. However, a composite of polyurethane foam and other materials has problems such as increased manufacturing costs and increased mass.

[0003] Patent Document 1 describes a polyurethane foam produced by foaming a raw material composition containing a high molecular weight polyoxyalkylene polyol, an organic polyisocyanate compound, a blowing agent, and a catalyst in a sealed mold. Meanwhile, Patent Document 2 describes a sound absorber having a porous inner body and a dense skin formed on the surface of the inner body. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2005-113134 A [Patent Document 2] Japanese Patent Application Publication No. 10-121597 Summary of the Invention [Problem to be solved by the invention]

[0005] Patent Document 1 describes a polyurethane foam with good sound absorption properties at around 500 Hz. Sound absorption properties in the low frequency range of around 500 Hz can be achieved by increasing the thickness of the sound absorbing material, but in Patent Document 1, in order to achieve sufficient sound absorption properties, it is necessary to thicken the film to a thickness of 26 mm. On the other hand, the sound absorber described in Patent Document 2 shows excellent sound absorption properties in the medium to high frequency range (2000 Hz or higher), but the sound absorption performance in the low frequency range (1000 Hz or lower, especially 500 Hz or lower) is not sufficient even when the thickness of the sound absorber is increased to 30 mm. Therefore, when the sound-absorbing materials described in Patent Documents 1 and 2 were applied to applications requiring thin films of up to about 10 mm (for example, fender liners and undercovers for vehicles), it was difficult to achieve sufficient sound-absorbing performance in the low frequency range.

[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a polyurethane foam and a vehicle soundproofing material that have a good sound absorption coefficient in the low frequency range (500 to 2000 Hz), can be made thin and lightweight while maintaining sound absorption performance equal to or greater than conventional levels, and can be used as a vehicle soundproofing material. [Means for solving the problem]

[0007] The above problem is solved by the following configuration. [1] A polyurethane foam having a surface layer and an internal foam layer formed therein, characterized in that the polyurethane foam has a thickness of 3 to 25 mm, a normal incident sound absorption coefficient at a frequency of 1000 Hz of 0.40 or more at a thickness of 10 mm, and a skeleton ratio SS / SI of 2.8 to 5.0, where SS is the skeleton ratio of the surface layer and SI is the skeleton ratio of the internal foam layer. [2] The polyurethane foam according to [1], wherein the skeleton ratio SS / SI is 2.8 to 4.0. [3] The polyurethane foam according to [1] or [2], wherein the skeleton ratio SS of the skin layer is 60% to 85%. [4] The polyurethane foam according to any one of [1] to [3], wherein the inner foam layer has a skeleton ratio SI of 24% to 30%. [5] The polyurethane foam according to any one of [1] to [4], wherein the skeletal ratio directly below the epidermis layer is 40% or more. [6] Density: 20 to 120 kg / m 3 The polyurethane foam according to any one of [1] to [5], [7] The polyurethane foam according to any one of [1] to [6], wherein the residual membrane ratio of the foam cells of the inner foam layer is 40% or more and less than 94%. [8] The polyurethane foam according to [7], wherein a value obtained by dividing the average skeletal diameter of the foamed cells by the average cell diameter is 0.10 to 0.50, and the average cell diameter of the foamed cells is 100 to 400 μm. [9] A soundproofing material for vehicles, comprising the polyurethane foam according to any one of [1] to [8].

[10] [9] A fender liner equipped with the vehicle soundproofing material described in

[10] [9]. Effect of the Invention

[0008] The polyurethane foam of the present invention has good sound absorption properties in the low frequency range of 500 to 2000 Hz even when it is thin, so it is suitable as a soundproofing material for vehicles. The frequency range in which the sound absorption coefficient is good is the frequency range of road noise, so it is suitable for use as a fender liner or undercover, especially as a fender liner. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The following describes an embodiment of the present invention, but the technical scope of the present invention is not limited to the embodiment described below, and various modifications can be made without departing from the spirit of the present invention.

[0010] [Polyurethane foam] The polyurethane foam of the present invention has a dense surface layer and an inner foam layer formed therein. The skin layer is formed so as to cover the outer surface of the polyurethane foam. The skin layer is a layer that greatly contributes to improving the sound absorption characteristics. The thickness of the skin layer is defined as the thickness from the sample surface to the part where the skeleton ratio is below 50% in the skeleton ratio measurement described later. The thickness of the surface layer is not particularly limited, but is preferably 0.2 to 1 mm, more preferably 0.2 to 0.6 mm. When the thickness is within this range, the polyurethane foam of the present invention can ensure sound absorption performance in the low frequency range of 500 to 2000 Hz. The inner foam layer refers to a porous inner body formed inside the skin layer.

[0011] The polyurethane foam of the present invention has a thickness of 3 to 25 mm, preferably 3 to 20 mm. When the thickness is equal to or greater than the above lower limit, good sound absorbing performance can be exhibited. On the other hand, when the thickness is equal to or less than the above upper limit, the polyurethane foam of the present invention is light in weight and yet tends to exhibit good sound absorbing performance. The polyurethane foam of the present invention has a normal incidence sound absorption coefficient of 0.40 or more at a frequency of 1000 Hz for a thickness of 10 mm. The normal incidence sound absorption coefficient is preferably 0.40 to 1, and more preferably 0.50 to 1. When the sound absorption coefficient is within this range, the polyurethane foam of the present invention has excellent sound absorption performance in the low frequency range of 500 to 2000 Hz. The polyurethane foam having a sound absorption coefficient within this range is suitable for use as a soundproofing material for vehicles. In particular, when the installation site is a narrowed portion or has a complex shape, the polyurethane foam is used in a thin state, and the advantages of the polyurethane foam of the present invention are fully utilized.

[0012] The sound absorption coefficient is measured using a 10 mm thick measurement sample cut from polyurethane foam with a sharp blade, in accordance with JIS A 1405-2:2007 "Measurement of sound absorption coefficient and impedance using an acoustic tube".

[0013] In the polyurethane foam of the present invention, when the skeleton ratio of the skin layer is SS and the skeleton ratio of the inner foam layer is SI, the skeleton ratio ratio SS / SI is 2.8 to 5.0, preferably 2.8 to 4.0. When the SS / SI ratio is above the lower limit, the density of the skin layer, which affects sound absorption, is high, blocking the transmission of low-frequency sound to the internal foam layer, and the interaction due to inertial forces improves the low-frequency sound absorption characteristics of the internal foam layer. On the other hand, if the SS / SI ratio is below the upper limit, the effect of sound reflection at the surface layer can be suppressed and the strength of the internal foam layer can be maintained. As a result, the polyurethane foam of the present invention has improved sound absorbing performance in the low frequency range of 500 to 2000 Hz.

[0014] The skeletal ratio is calculated from the results of cutting a polyurethane foam with a sharp blade to prepare a measurement sample, photographing a cross section of the sample in the thickness direction with an optical microscope. The detailed calculation method will be described later.

[0015] The skeletal ratio SS of the skin layer is defined as the average value of the skeletal ratios measured at a depth of 0.3 mm from the surface of the sample. Although there are no particular limitations on SS, it is preferably 60% to 85%, and more preferably 70% to 85%. When the value is within this range, the polyurethane foam of the present invention has improved sound absorbing performance in the low frequency range of 500 to 2000 Hz.

[0016] The skeletal ratio SI of the inner foam layer is defined as the average value of the skeletal ratios measured at a depth of 3.5 to 4.5 mm from the surface of the sample. The SI is not particularly limited, but is preferably 24% to 30%, more preferably 25% to 29%. When the value is within this range, the polyurethane foam of the present invention has improved sound absorbing performance in the low frequency range of 500 to 2000 Hz.

[0017] The skeletal ratio just below the skin layer is defined as the average value of the skeletal ratios measured at a depth just below the skin layer from the surface of the sample, with the position just below the skin layer being defined as a depth twice the thickness of the skin layer. The skeletal ratio just below the skin layer is not particularly limited, but is preferably 40% or more, and more preferably 40 to 70%. When the value is within this range, the polyurethane foam of the present invention has improved sound absorbing performance in the low frequency range of 500 to 2000 Hz.

[0018] The density of the polyurethane foam of the present invention is 20 to 120 kg / m 3 30-100kg / m 3 is preferable, and 55 to 90 kg / m 3 is more preferred. When the density is within this range, the polyurethane foam of the present invention can be made lighter while maintaining sound absorbing performance equal to or greater than that of conventional polyurethane foams. In particular, in recent years, there has been a strong demand for lighter soundproofing materials for vehicles, and the advantages of the polyurethane foam of the present invention can be utilized in this regard. Also, the polyurethane foam can be used in parts with complex shapes, such as fender liners.

[0019] The density is the density (unit: kg / m) measured according to JIS K 7222:2005 "Foamed plastics and rubber - Determination of apparent density". 3 ).

[0020] The residual membrane ratio of foam cells in the internal foam layer of the polyurethane foam of the present invention is 40% or more and less than 94%, preferably 40 to 90%, more preferably 50 to 85%, and even more preferably 55 to 85%. When the residual membrane ratio of the foam cells is within this range, the polyurethane foam of the present invention has excellent sound absorbing performance in the low frequency range of 500 to 2000 Hz. Furthermore, when the residual film ratio is within this range, shrinkage is unlikely to occur during molding of the polyurethane foam, making it easy to mold. The residual film ratio of the foam cells is calculated from the results of imaging the cross section of the measurement sample using an optical microscope. The detailed calculation conditions will be described later.

[0021] The average cell diameter of the foam cells of the inner foam layer is not particularly limited, but is preferably 100 to 400 μm, more preferably 150 to 350 μm, and even more preferably 150 to 300 μm. When the average cell diameter of the foam cells is within this range, the polyurethane foam of the present invention has excellent sound absorption performance in the low frequency range of 500 to 2000 Hz.

[0022] The value obtained by dividing the average skeletal diameter of the foam cells of the inner foam layer by the average cell diameter is not particularly limited, but is preferably from 0.10 to 0.50, more preferably from 0.15 to 0.45, and even more preferably from 0.27 to 0.45. When the value is within this range, the polyurethane foam of the present invention has improved sound absorbing performance in the low frequency range of 500 to 2000 Hz.

[0023] The average skeleton diameter and the average cell diameter of the internal foam layer are calculated from the results of photographing the cross section of the measurement sample using an optical microscope. Detailed calculation conditions will be described later.

[0024] [Manufacturing method of polyurethane foam] The polyurethane foam of the present invention can be produced, for example, by foaming a raw material composition G containing a polyoxyalkylene polyol A, an organic polyisocyanate compound B, a blowing agent C and a catalyst D.

[0025] <Raw material composition G> The raw material composition G contains a polyoxyalkylene polyol A, an organic polyisocyanate compound B, a blowing agent C, and a catalyst D. The raw material composition G is usually prepared by mixing a polyol system liquid H containing raw materials other than the organic polyisocyanate compound B with the organic polyisocyanate compound B.

[0026] (Polyoxyalkylene polyol A) Polyoxyalkylene polyol A (hereinafter referred to as "polyol A") is usually synthesized by ring-opening addition polymerization of an alkylene oxide to an initiator in the presence of a catalyst. Polyol A includes a trifunctional polyoxyalkylene polyol, i.e., a polyoxyalkylene polyol having three hydroxyl groups in one molecule. The polyoxyalkylene polyol other than the trifunctional polyoxyalkylene polyol is not particularly limited, and is, for example, a bifunctional or tetrafunctional or higher polyoxyalkylene polyol. The number of hydroxyl groups per molecule of polyol A (hereinafter referred to as "average number of hydroxyl groups") is not particularly limited as long as it is 2 or more, but is preferably 2 to 8, more preferably 2 to 4, further preferably 2.2 to 3.9, and even more preferably 2.4 to 3.7. When the average number of hydroxyl groups is within this range, the polyurethane foam tends to have a more appropriate softness, a more improved compression set, better mechanical properties such as elongation, and improved soundproofing performance. The number of hydroxyl groups in one molecule of the polyoxyalkylene polyol is equal to the number of active hydrogen-containing groups of the initiator used in the synthesis of the polyoxyalkylene polyol.

[0027] The number average molecular weight of polyol A is not particularly limited, but is preferably from 1000 to 20000, more preferably from 1000 to 16000, and even more preferably from 1500 to 12000. When the molecular weight is within this range, the residual membrane ratio of foamed cells in the polyurethane foam is easily kept within an appropriate range, and sound absorbing performance in the low frequency range of 500 to 2000 Hz is easily improved.

[0028] The number average molecular weight per hydroxyl group of polyol A (hereinafter referred to as "molecular weight / number of hydroxyl groups") is not particularly limited, but is usually 500 or more, preferably 500 to 5000, and more preferably 1000 to 3500. When the molecular weight / number of hydroxyl groups is within this range, the polyurethane foam is less likely to shrink and has better elasticity. In the present invention, polyoxyalkylene polyols having a molecular weight / number of hydroxyl groups of less than 500 are usually classified as crosslinking agent F, which will be described later.

[0029] The initiator used in the production of polyol A is preferably a compound having 2 to 8 active hydrogen-containing groups in one molecule, and such a compound is preferably a dihydric to octahydric polyhydric alcohol, a polyhydric phenol, or an amine. Examples of the dihydric to octahydric polyhydric alcohol include, but are not limited to, ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, dipropylene glycol, glycerin, trimethylolpropane, pentaerythritol, diglycerin, meso-erythritol, methyl glucoside, glucose, dextrose, sorbitol, and sucrose. The polyhydric phenols include, but are not limited to, bisphenol A, bisphenol F, pyrogallol, or hydroquinone. Examples of the amine include, but are not limited to, polyamines such as ethylenediamine, diethylenediamine, diaminodiphenylmethane, hexamethylenediamine, and propylenediamine, and condensation compounds obtained by condensation reaction of polyamines with phenolic resins or novolac resins. Also usable as an initiator are low molecular weight polyether polyols having hydroxyl groups at the molecular chain terminals obtained by ring-opening addition polymerization of a small amount of alkylene oxide to the polyhydric alcohols, polyhydric phenols, or amines. The molecular weight per hydroxyl group of such low molecular weight polyether polyols is usually 1200 or less, preferably 200 to 500, and more preferably 200 to 350.

[0030] As the initiator, a compound having 2 to 4 hydroxyl groups in one molecule is more preferable, and a dihydric to tetrahydric polyalcohol or a dihydric to tetrahydric low molecular weight polyether polyol is preferable. Among them, a polyol produced by using a trihydric or higher polyalcohol or a low molecular weight polyether polyol as an initiator has a better balance of soundproofing performance, foaming stability, and physical properties of the polyurethane foam. One type of initiator may be used alone, or two or more types may be used in combination.

[0031] The alkylene oxide is not particularly limited, but is preferably one or more selected from ethylene oxide, propylene oxide, butylene oxide, and styrene oxide, and more preferably one or more selected from ethylene oxide and propylene oxide. When the content of ethylene oxide is increased, the crystallinity of the polyoxyalkylene chain is improved, and the soft segment of the polyurethane tends to become rigid. The content of the unit derived from ethylene oxide in the polyoxyalkylene chain of the polyol A (hereinafter referred to as "EO content") is not particularly limited, but is preferably 0 to 20 mass% of the total mass of the polyoxyalkylene chain, and more preferably 0 to 15 mass%. When the EO content is within this range, the hydrophilicity of the polyoxyalkylene chain becomes more preferable, and the residual membrane ratio of the foamed cells in the obtained polyurethane foam tends to be within a more appropriate range.

[0032] A catalyst used in the ring-opening addition polymerization of an alkylene oxide to an initiator is a catalyst that has been used in the past, including, but not limited to, potassium hydroxide, sodium hydroxide, cesium hydroxide, a phosphazenium compound, a boron trifluoride compound, or a double metal cyanide complex.

[0033] The polyol A may contain polymer fine particles dispersed in the polyol A. The polymer fine particles are stably dispersed in the base polyol as a dispersion medium. Examples of the polymer fine particles include addition polymerization polymers and condensation polymerization polymers. The polymer constituting the polymer fine particles is preferably an addition polymerization polymer such as homopolymers or copolymers of acrylonitrile, styrene, alkyl methacrylate, alkyl acrylate, and other vinyl monomers, or a condensation polymerization polymer such as polyester, polyurea, polyurethane, or melamine resin, and more preferably a homopolymer or copolymer of acrylonitrile or styrene.

[0034] In the method for producing a polyurethane foam of the present invention, a polyol other than polyol A may be used in combination. Examples of such polyols include other high molecular weight polyols such as polyester polyols. The amount of polyol other than polyol A used is preferably 0 to 20 parts by mass, more preferably 0 to 10 parts by mass, and even more preferably 0 part by mass, i.e., none is used, relative to 100 parts by mass of the total of polyol A.

[0035] Hereinafter, the content of components other than polyol A in raw material composition G is defined as the content relative to 100 parts by mass of polyol A. The polyol A may be used alone or in combination of two or more kinds.

[0036] (Organic polyisocyanate compound B) The organic polyisocyanate compound B used in the production of the polyurethane foam of the present invention is not particularly limited, and examples thereof include at least one selected from the group consisting of aromatic polyisocyanates, alicyclic polyisocyanates, aliphatic polyisocyanates having two or more isocyanate groups, modified polyisocyanates obtained by modifying these, and polyisocyanates. Examples of the organic polyisocyanate compound B include toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), polymethylene polyphenylisocyanate (commonly known as crude MDI), xylylene diisocyanate (XDI), isophorone diisocyanate (IPDI) or hexamethylene diisocyanate (HMDI), prepolymer modified products, isocyanurate modified products, urea modified products and carbodiimide modified products of these polyisocyanates, and at least one selected from the group consisting of TDI, MDI, crude MDI and modified products thereof is preferable in terms of availability. TDI may be any of 2,4-TDI and 2,6-TDI, or may be a mixture. MDI may be any of 2,2'-MDI, 2,4'-MDI and 4,4'-MDI, or may be a mixture of two or three of these. As the organic polyisocyanate compound B, TDI is particularly preferable.

[0037] The content of organic polyisocyanate compound B in raw material composition G is not particularly limited, but is preferably an amount such that the total number of moles of isocyanate groups in organic polyisocyanate compound B is divided by the total number of moles of hydroxyl groups in polyol A and multiplied by 100 (isocyanate index) is 75 to 120, more preferably 80 to 120, and even more preferably 80 to 110. When the isocyanate index is within this range, curing can be sufficiently progressed, and a foam with an appropriate degree of curing can be obtained without excessive curing. The organic polyisocyanate compound B may be used alone or in combination of two or more kinds.

[0038] (Foaming agent C) The blowing agent used in producing the polyurethane foam of the present invention comprises water. In addition, a blowing agent other than water can be used to reduce the density of the foam. As a blowing agent other than water, an inactive compound having a low boiling point is preferable. Examples of such an inactive compound include an inactive gas and a saturated hydrocarbon (hereinafter referred to as "saturated hydrocarbon X") having a boiling point of 70°C or less and further including a hydrocarbon compound having 8 or less carbon atoms, in which a part of the hydrogen atoms bonded to the carbon atoms of the hydrocarbon compound may be substituted with halogen atoms. The halogen atom is, for example, a chlorine atom or a fluorine atom. Examples of the saturated hydrocarbon X include, but are not limited to, butane, pentane, hexane, dichloromethane (methylene chloride), trichloroethane, and various fluorocarbon compounds.

[0039] The content of water as the blowing agent C in the raw material composition G is preferably 1.5 parts by mass or more, and more preferably 2 to 5 parts by mass, per 100 parts by mass of the polyol A. By setting the content within this range, foaming can be sufficiently promoted, and the density of the foam can be easily set within the desired range. The content of the blowing agent other than water in the raw material composition G is not particularly limited, but is preferably 0 to 25 parts by mass, and more preferably 0 to 20 parts by mass, per 100 parts by mass of the polyol A. The foaming agent C may be used alone or in combination of two or more kinds.

[0040] (Catalyst D) Catalyst D used in the production of the polyurethane foam of the present invention is at least one selected from the group consisting of amine-based catalysts and tin-based catalysts. Catalyst D is a catalyst used when reacting a polyoxyalkylene polyol with an organic polyisocyanate compound. The catalyst D may be used alone or in combination of two or more kinds.

[0041] Examples of the amine catalyst include, but are not limited to, triethylenediamine, bis(2-dimethylaminoethyl)ether, N,N,N',N'-tetramethylhexamethylenediamine, N,N-dimethylaminoethoxyethoxyethanol, N,N-dimethylamino-6-hexanol, N,N-dimethylaminoethoxyethanol, a compound in which 2 moles of ethylene oxide are added to N,N-dimethylaminoethoxyethanol, or 5-(N,N-dimethyl)amino-3-methyl-1-pentanol.

[0042] The content of the amine catalyst in raw material composition G is not particularly limited, but is preferably 0.1 to 5.0 parts by mass, and more preferably 0.2 to 3.0 parts by mass, per 100 parts by mass of polyol A. The amine catalyst may be used alone or in combination of two or more kinds.

[0043] The tin-based catalysts include, but are not limited to, tin 2-ethylhexanoate, di-n-butyltin oxide, di-n-butyltin dilaurate, di-n-butyltin diacetate, di-n-octyltin oxide, di-n-octyltin dilaurate, monobutyltin trichloride, di-n-butyltin dialkyl mercaptan, and di-n-octyltin dialkyl mercaptan.

[0044] The content of the tin-based catalyst in raw material composition G is not particularly limited, but is preferably 1.0 part by mass or less, and more preferably 0.005 to 1.0 part by mass, per 100 parts by mass of polyol A. The tin-based catalysts may be used alone or in combination of two or more kinds.

[0045] (Foam stabilizer E) The raw material composition G used in the production of the polyurethane foam of the present invention may further contain a foam stabilizer E. Examples of the foam stabilizer E include, but are not limited to, silicone-based foam stabilizers and fluorine-containing compound-based foam stabilizers. When the raw material composition G contains the foam stabilizer E, good foam can be formed. The content of the foam stabilizer E in the raw material composition G is not particularly limited, but is preferably 0.1 to 5.0 parts by mass, more preferably 0.3 to 4.0 parts by mass, and even more preferably 0.5 to 3.0 parts by mass, per 100 parts by mass of the polyol A. The foam stabilizer E may be used alone or in combination of two or more kinds.

[0046] (Crosslinker F) The raw material composition G used in the production of the polyurethane foam of the present invention may further contain a crosslinking agent F. The crosslinking agent F is preferably a compound having two or more active hydrogen-containing groups selected from a hydroxyl group, a primary amino group, and a secondary amino group. The number of active hydrogen-containing groups is preferably 2 to 8. The molecular weight of the crosslinking agent per active hydrogen-containing group is preferably less than 500.

[0047] Examples of the crosslinking agent F include ethylene glycol, propylene glycol, 1,4-butanediol, neopentyl glycol, 1,6-hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, glycerin, trimethylolpropane, pentaerythritol, diglycerin, monoethanolamine, diethanolamine, triethanolamine, bisphenol A, ethylenediamine, 3,5-diethyl-2,4-diaminotoluene, 3,5-diethyl-2,6-diaminotoluene, 2-chloro-p-phenylenediamine, 3,5 -bis(methylthio)-2,4-diaminotoluene, 3,5-bis(methylthio)-2,6-diaminotoluene, 1-trifluoromethyl-3,5-diaminobenzene, 1-trifluoromethyl-4-chloro-3,5-diaminobenzene, 2,4-toluenediamine, 2,6-toluenediamine, bis(3,5-dimethyl-4-aminophenyl)methane, 4,4'-diaminodiphenylmethane, m-xylylenediamine, 1,4-diaminohexane, 1,3-bis(aminomethyl)cyclohexane and isophoronediamine are included, but are not limited thereto. In addition, as the crosslinking agent F, the above-mentioned polyoxyalkylene polyol having a molecular weight / hydroxyl group number of less than 500 can also be used.

[0048] The content of the crosslinking agent F in the raw material composition G is not particularly limited, but is preferably 0.1 to 20 parts by mass, and more preferably 0.5 to 10 parts by mass, per 100 parts by mass of the polyol A. The crosslinking agent F may be used alone or in combination of two or more kinds.

[0049] (Additives) The raw material composition G used in the production of the polyurethane foam of the present invention may further contain additives. Examples of the additives include various known additives or auxiliaries such as emulsifiers, antioxidants, ultraviolet absorbers, and other anti-aging agents, fillers such as calcium carbonate or barium sulfate, plasticizers, colorants, flame retardants, anti-fungal agents, and foam breakers, but are not limited to these, and additives that have conventionally been used in polyurethane foams can be used. The content of the additives in the raw material composition G is not particularly limited as long as it does not impair the effects of the present invention.

[0050] <Molding method> In the method for producing the polyurethane foam of the present invention, a molding method in which the raw material composition G is injected into a closed mold is preferred. As the molding method, for example, a molding method called mold foaming can be mentioned.

[0051] [Soundproofing materials for vehicles] The vehicle soundproofing material of the present invention contains the above-mentioned polyurethane foam. The vehicle is preferably a car. The polyurethane foam of the present invention has a thin thickness and good sound absorption properties in the low frequency range of 500 to 2000 Hz, making it suitable as a soundproofing material for vehicles. The frequency range in which the sound absorption coefficient is good is the frequency range of road noise, so the foam is suitable for use as a fender liner or undercover, particularly as a fender liner. EXAMPLES

[0052] The present invention will be described in more detail below with reference to examples. However, the technical scope of the present invention is not limited to the examples described below, and various modifications can be made without departing from the spirit of the present invention.

[0053] [Synthesis example] The polyoxyalkylene polyols were synthesized according to the following procedure.

[0054] <Synthesis Example 1> Polyoxyalkylene polyol A1 was synthesized by ring-opening addition polymerization of propylene oxide using glycerin as an initiator in the presence of potassium hydroxide catalyst, and then ring-opening addition polymerization of ethylene oxide.

[0055] <Synthesis Example 2> The polyoxyalkylene polyol A1 obtained above was used as a dispersion medium, and acrylonitrile polymer fine particles (30% by mass) were dispersed therein to obtain polyoxyalkylene polyol A2.

[0056] <Synthesis Example 3> A double metal cyanide complex catalyst (hereinafter referred to as "DMC catalyst") was produced by the production method described in

[0021] to

[0034] of JP2016-006203A. In the presence of a DMC catalyst, propylene oxide was subjected to ring-opening addition polymerization using glycerin as an initiator, and then ethylene oxide was subjected to ring-opening addition polymerization using KOH to obtain polyoxyalkylene polyol A3.

[0057] <Synthesis Example 4> Polyoxyalkylene polyol A4 was synthesized by ring-opening addition polymerization of propylene oxide using glycerin as an initiator in the presence of potassium hydroxide catalyst, and then ring-opening addition polymerization of ethylene oxide.

[0058] <Synthesis Example 5> Polyoxyalkylene polyol A5 was synthesized by ring-opening addition polymerization of propylene oxide with glycerin as an initiator in the presence of potassium hydroxide catalyst.

[0059] <Synthesis Example 6> Polyoxyalkylene polyol A6 was synthesized by ring-opening addition polymerization of propylene oxide using glycerin as an initiator in the presence of potassium hydroxide catalyst, and then ring-opening addition polymerization of ethylene oxide. The number average molecular weight, the number of hydroxyl groups per molecule, the molecular weight per hydroxyl group, and the EO content of each of the polyoxyalkylene polyols A1 to A6 are as shown in Table 1.

[0060] [Table 1]

[0061] In Table 1, the EO content refers to the content (% by mass) of units derived from ethylene oxide in the polyoxyalkylene chain of the polyoxyalkylene polyol, and the PO content refers to the content (% by mass) of units derived from propylene oxide in the polyoxyalkylene chain of the polyoxyalkylene polyol.

[0062] [Example 1] An aluminum mold measuring 150 mm in length, width and height was prepared. As shown in Table 2, 60 parts by mass of polyoxyalkylene polyol A1, 40 parts by mass of polyoxyalkylene polyol A2, 3 parts by mass of foaming agent C1, 0.3 parts by mass of catalyst D1, 0.05 parts by mass of catalyst D2, 3 parts by mass of foam stabilizer E2, and 3 parts by mass of crosslinking agent F1 were placed in a container and mixed for 30 seconds at 3000 rpm using a high-speed mixer. A mixture containing raw materials other than the organic polyisocyanate compound (hereinafter referred to as "polyol system liquid 1") was obtained. 39.4 parts by mass of the organic polyisocyanate compound B2 was added to the polyol system liquid 1, and mixed for 5 seconds at 3000 rpm using the high-speed mixer (described above) to obtain a raw material composition (hereinafter referred to as "raw material composition 1"). The upper and lower mold temperatures of a mold prepared in advance were raised to 60°C, and then Raw Material Composition 1 was poured in and foamed and cured. After 3 minutes, the cured product was removed from the mold and crushed to degas, yielding a flexible polyurethane foam (hereinafter referred to as "Polyurethane Foam 1"). The production of polyol system liquid 1, raw material composition 1 and polyurethane foam 1 was carried out in an environment in which both room temperature and liquid temperature were 25°C.

[0063] [Example 2] A mixture containing raw materials other than an organic polyisocyanate compound (hereinafter referred to as "polyol system liquid 2") was obtained in the same manner as in Example 1, except that the amount of foaming agent C1 added was changed to 1 part and catalyst D2 was not used. A raw material composition (hereinafter referred to as "raw material composition 2") was obtained by adding 18.5 parts by mass of organic polyisocyanate compound B2 in the same manner as in Example 1. A flexible polyurethane foam (hereinafter referred to as "polyurethane foam 2") was obtained in the same manner as in Example 1, except that raw material composition 2 was used.

[0064] [Example 3] A mixture containing raw materials other than an organic polyisocyanate compound (hereinafter referred to as "polyol system liquid 3") was obtained in the same manner as in Example 2, except that the amount of foaming agent C1 added was changed to 5 parts. A raw material composition (hereinafter referred to as "raw material composition 3") was obtained by adding 60.2 parts by mass of organic polyisocyanate compound B2 in the same manner as in Example 2. A flexible polyurethane foam (hereinafter referred to as "polyurethane foam 3") was obtained in the same manner as in Example 1, except that raw material composition 3 was used.

[0065] [Example 4] As shown in Table 2, 8 parts by mass of polyoxyalkylene polyol A3, 3 parts by mass of polyoxyalkylene polyol A4, 72 parts by mass of polyoxyalkylene polyol A5, 20 parts by mass of polyoxyalkylene polyol A6, 2.35 parts by mass of foaming agent C1, 0.6 parts by mass of catalyst D1, 0.3 parts by mass of catalyst D3, 0.3 parts by mass of catalyst D4, and 0.4 parts by mass of foam stabilizer E1 were placed in a container and mixed at 3000 rpm for 30 seconds using a high-speed mixer. A mixture containing raw materials other than the organic polyisocyanate compound (hereinafter referred to as "polyol system liquid 4"). 29.9 parts by mass of organic polyisocyanate compound B1 was added to polyol system liquid 4, and mixed for 5 seconds at 3000 rpm using a high-speed mixer (described above). A raw material composition (hereinafter referred to as "raw material composition 4") was obtained. A flexible polyurethane foam (hereinafter referred to as "polyurethane foam 4") was obtained in the same manner as in Example 1, except that raw material composition 4 was used. Polyurethane foams 1 to 4 were left to stand for 24 hours or more in a room adjusted to a temperature of 23° C. and a humidity of 50% RH.

[0066] [Table 2]

[0067] The symbols in Table 2 have the following meanings: A: Polyoxyalkylene polyol A1 Polyoxyalkylene polyol A1 synthesized in Synthesis Example 1 A2 Polyoxyalkylene polyol A2 synthesized in Synthesis Example 2 A3 Polyoxyalkylene polyol A3 synthesized in Synthesis Example 3 A4 Polyoxyalkylene polyol A4 synthesized in Synthesis Example 4 A5 Polyoxyalkylene polyol A5 synthesized in Synthesis Example 5 A6 Polyoxyalkylene polyol A6 synthesized in Synthesis Example 6

[0068] B: Organic polyisocyanate compound B1 Mixture of TDI and MDI (Coronate 1025, Tosoh Corporation) A mixture of 2,4-TDI, 2,6-TDI and crude MDI with a mass ratio of 2,4-TDI / 2,6-TDI / crude MDI = 40 / 10 / 50 Isocyanate group content: 39.7% by mass B2 Mixture of TDI and MDI (Coronate 1021, Tosoh Corporation) A mixture of 2,4-TDI, 2,6-TDI and crude MDI with a mass ratio of 2,4-TDI / 2,6-TDI / crude MDI = 64 / 16 / 20 Isocyanate group content: 44.8% by mass

[0069] C: Foaming agent ·C1 Water

[0070] D:Catalyst D1 Dipropylene glycol solution of triethylenediamine (TEDA (registered trademark) L-33, manufactured by Tosoh Corporation) Amine catalyst D2 Tin 2-ethylhexanoate (DABCO(R) T-9, EVONIK) D3 Dipropylene glycol solution of bis[(2-dimethylamino)ethyl]ether (TOYOCAT(R) ET, manufactured by Tosoh Corporation) D4 1-isobutyl-2-methylimidazole (NC-IM, Sankyo Air Products)

[0071] E: Foam stabilizer E1 Silicone foam stabilizer (SRX-274C, Dow Corning) E2 Silicone foam stabilizer (TEGOSTAB (registered trademark) B8737 LF2, manufactured by EVONIK)

[0072] F: Crosslinking agent F1: Crosslinking agent (polyol having a molecular weight of 400, functional groups of 4, and an EO content of 100% by mass) The EO content of F1, 100% by mass, means that the units derived from ethylene oxide among the units derived from alkylene oxide in the polyoxyalkylene chain, are 100% by mass.

[0073] [Evaluation method] The polyurethane foams 1 to 4 obtained in Examples 1 to 4 were cut with a sharp blade to prepare a measurement sample. The thickness of any five points of the measurement sample was measured with a dial thickness gauge type film thickness measuring instrument (manufactured by Ozaki Manufacturing Co., Ltd., Model: G), and the average thickness was calculated to be 10 mm. Using the measurement sample, the sound absorption coefficient, density, remaining film ratio, average cell diameter, average skeletal diameter, value obtained by dividing the average skeletal diameter by the average cell diameter, skeletal ratio (skin layer skeletal ratio SS, inner foam layer skeletal ratio SI, SS / SI, skeletal ratio directly below the skin layer), and skin layer thickness were evaluated by the methods described below, and the results are shown in Table 3.

[0074] [Table 3]

[0075] <Sound absorption rate> The normal incidence sound absorption coefficient (sound absorption coefficient) was measured in the 500 to 2000 Hz range by a method conforming to JIS A 1405-2:2007 "Measurement of sound absorption coefficient and impedance using an acoustic tube." The following equipment was used for the measurement. Vertical incidence sound absorption measurement tube (40mmφ, manufactured by Nihon Onkyo Engineering Co., Ltd.) Analysis software (WinZacMTX VER.5.0, manufactured by Nihon Onkyo Engineering Co., Ltd.) Power amplifier (AP15d, FOSTEX) Microphone (46BD, GRAS) Microphone amplifier (12AQ, GRAS) Audio interface (Fireface UC, RME)

[0076] <density> The density was measured according to JIS K 7222:2005 "Foamed plastics and rubber - Determination of apparent density". The density was measured for the entire polyurethane foam.

[0077] <Remaining film rate> The cross section of the measurement sample was photographed at a magnification of 150x using an optical microscope 1 (VHX-1000, manufactured by Keyence Corporation). The part of the internal foam layer where the cell skeleton could be confirmed over the entire circumference and where there was no obvious destruction of the peripheral skeleton was the object of observation. When an undamaged membrane was present on the inner periphery of the cell skeleton being observed, it was judged that "membrane remains." When there was no membrane on the inner periphery of the cell skeleton to be observed, or the membrane was broken even partially, it was judged as "no membrane remaining." The cross section of the measurement sample was photographed at 10 points, 100 cell skeletons were observed, the number of "with remaining membrane" and "without remaining membrane" were counted, and the ratio of "with remaining membrane" was calculated as a percentage. The calculated percentage was taken as the remaining membrane ratio.

[0078] <Average skeletal diameter> The cross section of the measurement sample was photographed at a magnification of 150 times using an optical microscope 1. The part of the internal foam layer where the boundaries between the skeleton and the cell and membrane parts could be clearly observed was observed. The average skeleton diameter of the observed skeleton part was measured using image processing software (ImageJ, manufactured by the National Institutes of Health, USA). For skeletons with a constricted shape, the narrowest diameter was taken as the skeleton diameter of the skeleton part. The cross section of the measurement sample was photographed at 10 points, the skeletal diameters of 70 observation targets were measured, and the average skeletal diameter was calculated from the arithmetic mean.

[0079] <Average cell diameter> The cross section of the measurement sample was photographed at a magnification of 150 times using an optical microscope 1. The part of the internal foam layer where the cell skeleton could be confirmed over the entire periphery was the object of observation. The outline of the inner periphery of the cell to be observed was extracted using image processing software (ImageJ, National Institutes of Health, USA), and the area enclosed by the outline was calculated. The diameter of a circle with the same area as the calculated area (equivalent circle diameter) was calculated and defined as the cell diameter of the cell to be observed. The cross section of the measurement sample was photographed at 10 points, the cell diameters of 80 observed objects were measured, and the average cell diameter was calculated from the arithmetic mean.

[0080] <Average skeletal diameter / average cell diameter> From the average skeletal diameter and the average cell diameter obtained by the above-mentioned methods, a value was calculated by dividing the average skeletal diameter by the average cell diameter.

[0081] <Bone ratio> The cross section of the measurement sample was photographed using an optical microscope 1. Then, the photographed image was cut into an area of ​​2.5 mm × 3.5 mm using image processing software (ImageJ, manufactured by the National Institutes of Health, USA). The cut-out images were subjected to binarization processing using discriminant analysis (Otsu's binarization). In the above binarized image, the area ratio of the black parts was calculated for each region of 0.02 mm x 3.5 mm, and the area ratio at each position was obtained while scanning the analysis region in the sample thickness direction in 0.02 mm increments, and the distribution of the skeleton ratio in the sample thickness direction (skeleton ratio profile) was calculated. The cross section of the measurement sample was imaged at five or more points, and the skeletal ratio was calculated by the arithmetic mean of the skeletal ratio profiles obtained from each image.

[0082] <Skin layer ratio SS> The skin layer skeletal ratio SS was calculated from the arithmetic average of the skeletal ratio profile measured at a depth of 0.3 mm from the surface of the polyurethane foam.

[0083] <Inner foam layer skeleton ratio SI> The inner foam layer skeletal ratio SI was calculated from the arithmetic mean of the skeletal ratio profile measured at a depth of 3.5 to 4.5 mm from the surface of the polyurethane foam.

[0084] <ss si> From the skin layer skeletal ratio SS and the inner foamed layer skeletal ratio SI determined by the above-mentioned method, a value was calculated by dividing the skin layer skeletal ratio SS by the inner foamed layer skeletal ratio SI.

[0085] <Skin layer thickness> In the skeletal ratio profile obtained by the above-mentioned method, the analysis region was scanned in the sample thickness direction in 0.02 mm increments from the sample surface to the part where the skeletal ratio was below 50%, and this was calculated as the skin layer thickness.

[0086] [Results explanation] Example 1 corresponds to the embodiment, and Examples 2 to 4 correspond to the comparative examples. The polyurethane foam of Example 1 has a residual film ratio within a specific range, and is excellent not only in sound absorption characteristics at a low frequency of 1000 Hz, but also in sound absorption performance in the low frequency range. In addition, since the polyurethane foam of Example 1 has high sound absorption performance even though it is thin, it can be introduced into areas that require weight reduction and thinning to achieve a high sound absorption environment. Although the polyurethane foam of Example 2 had a higher density than the polyurethane foam of Example 1, the SS / SI did not satisfy the range of the present invention and the residual film rate was also high, so sufficient sound absorption properties were not obtained. The polyurethane foam of Example 3 did not satisfy the range of the present invention for SS / SI, and furthermore, had a lower density and a lower film residual rate than the polyurethane foam of Example 1, so that the sound absorption characteristics in the low frequency range were insufficient. Although the polyurethane foam of Example 4 had a higher density than the polyurethane foam of Example 1, the SS / SI was outside the range of the present invention, and therefore sufficient sound absorbing properties were not obtained. [Industrial Applicability]

[0087] The polyurethane foam of the present invention has a thin thickness and good sound absorption properties in the low frequency range of 500 to 2000 Hz, making it suitable as a soundproofing material for vehicles. The frequency range in which the sound absorption coefficient is good is the frequency range of road noise, so the foam is suitable for use as a fender liner or undercover, particularly as a fender liner. The entire contents of the specification, claims and abstract of Japanese Patent Application No. 2019-236123, filed on December 26, 2019, are hereby incorporated by reference as the disclosure of the specification of the present invention.< / ss>

Claims

1. A polyurethane foam having a surface layer and an inner foam layer formed therein, The thickness is 3 to 25 mm, and the normal incidence sound absorption coefficient at a frequency of 1000 Hz is 0.50 or more at a thickness of 10 mm, A polyurethane foam characterized in that a skeleton ratio SS / SI, where SS is the skeleton ratio of the skin layer and SI is the skeleton ratio of the inner foam layer, is 2.8 to 5.

0.

2. A polyurethane foam as described in claim 1, wherein the skin layer is a layer having a thickness from the sample surface to the part where the skeletal ratio falls below 50% in the skeletal ratio measurement, and the thickness is 0.2 to 1 mm.

3. The polyurethane foam according to claim 1 or 2, wherein the skeleton ratio SS / SI is 2.8 to 4.

0.

4. The polyurethane foam according to any one of claims 1 to 3, wherein the skeleton ratio SS of the surface layer is 60% to 85%.

5. The polyurethane foam according to any one of claims 1 to 4, wherein the skeleton ratio SI of the inner foam layer is 24% to 30%.

6. The polyurethane foam according to any one of claims 1 to 5, wherein a skeleton ratio directly below the surface layer is 40% or more.

7. Density: 20-120 kg / m 3 The polyurethane foam according to any one of claims 1 to 6,

8. The polyurethane foam according to any one of claims 1 to 7, wherein a residual membrane ratio of foam cells of the internal foam layer is 40% or more and less than 94%.

9. 9. The polyurethane foam according to claim 8, wherein a value obtained by dividing the average skeletal diameter of the foamed cells by the average cell diameter is 0.10 to 0.50, and the average cell diameter of the foamed cells is 100 to 400 μm.

10. A soundproofing material for vehicles comprising the polyurethane foam according to any one of claims 1 to 9.

11. A fender liner comprising the vehicle soundproofing material according to claim 10.

Citation Information

Patent Citations

  • Sound absorption body and vehicle using the same

    JP1998121597A

  • Foam sound absorbing material

    JP1999124496A

  • Sound absorbing material of foamed polyurethane

    JP2003300294A

  • Flexible polyurethane foam and its preparation process

    JP2005113134A

  • Rigid polyurethane foam

    JP2005272806A